Co-Morbidities in Children with Cerebral Palsy Undergoing Early Spine Fusion for Scoliosis (Journal of Nobel Medical College, 2014)
Introduction: Children with Cerebral Palsy (CP) may have multisystem involvement the occurrence of which increases with severity of involvement. Scoliosis is also found to be more prevalent in severely involved children with CP. Aims: This study aimed to describe co-morbidities in children with CP undergoing early spine fusion for scoliosis. Methods: A retrospective review of patients with CP Scoliosis between 1989 and 206 who were